Personal and Professional Balance Among Freelance Workers: A Statusquo Analysis - Nerisa B. Abug; Bhrendelyn B. Navales; Rejeanne S. Calderon; Eunice Rain De Jesus; Eileen N. Garcia (Garuda Prestasi Nusantara Consulting, 2023)
Personal and professional balance is important not just for personal health and relationships, but also, for employees’ level of productivity and organizational performance. The main objective is to determine the personal and professional balance of freelance workers during the pandemic. This study gathered the data using the descriptive research method. With the help of online survey questionnaires, the researchers conveniently selected 40 freelance workers to know the personal and professional balance of freelance workers in selected areas of Cavite. Considerably, the results revealed that the majority of them were between the ages of 18 and 25, single, in their first year of college, and had been working as freelancers for less than a year. Also, the majority of freelancers’ work was related to marketing, editing, IT, and computer industries. The respondents agreed that professional life interferes with their personal life. Moreover, the respondents concured that stress, the need to reply to everything right away, and providing others with access around-the-clock are obstacles to striking a balance between personal and professional lives. This study is recommended to provide specific and attainable professional management design particularly for freelance workers. Keywords : freelance workers, personal and professional balance, statusquo analysis